How to build and share an experiential knowledge in public health?. (13th November 2019) - Laurent, A; Ferron, C; Lombrail, P; Berry, P; Frattini, M O; Berdougo, F; Rusch, E
Abstract: : Health promotion stakeholders are encouraged to base their intervention strategies on evidence. However, the evidence produced by public health research is outcome-based and provides little information on "how to act?" It is necessary to complete this evidence with experiential data constituting an evidence of a different nature, answering questions about organizations, skills and tools mobilized to achieve the results, and valuing skilled actors' knowledge and good practice. For two years, a group of 15 French organizations has been working on capitalization and sharing experiential knowledge. This work is part of the setting up of a national evidence platform. After a benchmarking phase, the group developed and tested a capitalization method which focuses on the collection and analysis of qualitative data and aims to explain the contexts and processes at work in the actions: knowledge and skills, strategies, perceived challenges and facilitating factors, key moments. The group also worked on the structure, content and use of a shareable document. The test has shown the pedagogical interest of the method for the actors who were invited to develop a reflective thinking about their action, as well as the relevance of this method to build experiential knowledge. The ongoing group's work concerns the dissemination of collected data. A practical guide for stakeholders is being finalised. The group is defining the selection process of the initiatives to be valued, in particular with regard to results that make sense for all stakeholders. The main difficulty of the approach - its low level of recognition and entrenchment in public health - will be discussed during the presentation, as well as the necessity to ensure the legitimacy of this approach in a context where the notion of evidence is centered on quantitative data produced with an objective defined "a priori" and in a controlled context. Key messages: This work opens the way for an original reflection in public health to build a shareable experiential knowledge, and to valorize and strengthen field actors' practical expertise. This work has pedagogical, political, scientific and informational impacts. It contributes to knowledge transfer and provides self-training, a practical vision of policies, and questions for research.